Cachexia: a systemic consequence of progressive, unresolved disease - Ferrer, Miriam Coronel; Anthony, Tracy G.; Ayres, Janelle S.; Biffi, Giulia; Brown, Justin C.; Caan, Bette J.; Cespedes Feliciano, Elizabeth M.; Coll, Anthony P.; Dunne, Richard F.; Goncalves, Marcus D.; Grethlein, Jonas; Heymsfield, Steven B.; et al. (Cell, 2023)
Cachexia, a systemic wasting condition, is considered a late consequence of diseases, including cancer, organ failure, or infections, and contributes to significant morbidity and mortality. The induction process and mechanistic progression of cachexia are incompletely understood. Refocusing academic efforts away from advanced cachexia to the etiology of cachexia may enable discoveries of new therapeutic approaches. Here, we review drivers, mechanisms, organismal predispositions, evidence for multi-organ interaction, model systems, clinical research, trials, and care provision from early onset to late cachexia. Evidence is emerging that distinct inflammatory, metabolic, and neuro-modulatory drivers can initiate processes that ultimately converge on advanced cachexia.